In vitro anthelmintic activity of hydroethanolic extract of Artemisia herba aba and Juniperus phoenicea on abomasal Teladorsagia circumcincta of sheep. - Lamine, Zinelabiddine; Abdennour, Azizi; Abderrahman, Rahmani; Mouna, Derdour; Madjid, Tlidjane (Archives of Veterinary Science, 2024)
The present study aimed to evaluate the in vitro anthelmintic activity of Juniperus phoenicea and Artemisia herba-alba against abomasal nematodes collected from naturally infected sheep. The anthelmintic activities of the extracts were assessed using egg hatch inhibition (EHIA) and adult motility assays (AMA) against Teladorsagia circumcincta. The parasites were stored in phosphate-buffered saline (PBS) until the in vitro assessment began. The leaf powders of J. phoenicea and A. herba-alba were extracted using the maceration procedure. Briefly, the leaf powders were mixed with a sufficient quantity of 99% ethanol and distilled water (80%/20%). The extracts were dissolved in a 3% dimethyl sulfoxide (DMSO) solution to improve water solubility. The hydroethanolic extracts were tested at concentrations of 1.562, 3.125, 6.25, 12.5, and 25 mg/ml. Adult motile worms were individually subjected to each treatment at laboratory temperature. The PBS and albendazole (25 mg/ml) were prepared and used as negative and positive controls, respectively. The test was repeated five times for each concentration. The results showed that both plant extracts exhibited anthelmintic effects. A. herba-alba extract at 25 mg/ml inhibited the motility of all T. circumcincta adult worms within 1 hour of administration, while J. phoenicea extract caused 100% mortality of adult worms after 4 hours at the same concentration. Neither of the extracts, at 1.562 mg/ml, had any inhibitory effect on motility. At 25 mg/ml, the A. herba-alba (98.67%) and J. phoenicea (96.24%) showed high activity with an inhibitory effect on hatchability compared to the other tested concentrations. The findings of the present study showed that hydroethanolic extracts of A. herba-alba and J. phoenicea leaves had in vitro anthelmintic activity on eggs and adult T. circumcincta of sheep.